Second Language Identity of Chinese Junior High School EFL Learners: Its Construction and Sources - Han, Yazhuo (Transactions on Social Science, Education and Humanities Research, 2024)
Language learning is widely agreed to be closely related to individuals’ identity constructions. In recent years, identity research has gained more attention for its constructed and dynamic nature could provide a more insightful view of language learning processes and thus help better improve language learning and teaching. Many existing studies on language identities have been conducted in English as a Second Language (ESL) contexts and focused on more mature English learners. However, studies conducted in English as Foreign Language (EFL) contexts like China, especially those focused on younger learners were inadequate. With a qualitative research design and using a series of narrative data collection methods, the current research explored the second language identity of Chinese Junior High School (CJHS) EFL learners both in terms of its construction and sources. The findings of the research suggested that CJHS EFL learners’ second language identity experienced a downtrend flux as their English learning moved on. Factors including social context in China, experiences in English classes, the direct connection between English and their daily life and intimate people around weave together to build their second language identities. Several pedagogical implications were also proposed to help CJHS EFL learners negotiate their second language identity so that they could better locate themselves in the more globalized world.